Principal Managerial Competence in Improving the Performance of Educators in School - Hamidah Hamidah; Aan Komariah; Nur Aedi; Eka Prihatin (Universitas Negeri Malang, 2026)
Abstract: this research aimed to investigate the role and impact of the principal's managerial competence in improving the performance of teaching staff at SMPN 3 Bandar Dua. The research method used is a qualitative approach with a case study approach. Data was collected through in-depth interviews with school principals, teachers, and direct observation in the school environment. The results of the data analysis show that the principal's managerial competence has a crucial role in creating an effective and supportive learning environment. Human resource management, curriculum development, learning monitoring, and effective communication emerged as important aspects of these competencies. The findings of this study provide valuable insights into how school principals can become agents of change in improving teacher performance through the development of appropriate and measurable managerial competencies. Keywords: Managerial Competence, The Performance of Educators, School Principals